KONTRIBUSI LOCUS OF CONTROL DAN PERFEKSIONIS TERHADAP PROKRASTINASI AKADEMIK SISWA SERTA IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING DI SMAN 10 PADANG - Desy Murni Lasari (Jurnal Sosial Humaniora Sigli, 2020)
Academic procrastination was one of behavior of students who defer to the task. Academic procrastination was influenced by various factors among which are the locus of control and perfectionist. This study aimed to described: (1) locus of control of students SMAN 10 Padang, (2) perfectionist of students SMAN 10 Padang, (3) academic procrastination of students SMAN 10 Padang, (4) contribution locus of control toward academic procrastination students SMAN 10 Padang, (5) contribution of perfectionist towardacademic procrastination studentsSMAN 10Padang, (6) contribution locus of control and perfectionist toward academic procrastination students SMAN 10 Padang.This study used a quantitative approach with descriptive correlational method. The population in this research were students in grade X and XI of SMAN 10 Padang many as 571 students. Samples were obtained as many 235 students with using Proportional Stratified Random Sampling technique. The instruments of this research were the Inventory and Likert scale model. The data obtained were analyzed by using simple regression, and multiple regression.The research finding were: (1) locus of control in average were at internal category, (2) perfectionist in average were atmoderate category, (3) the academic procrastination in average were at moderate category, (4) the locus of control are contribution significant to academic procrastination by 21.3%, (5) the perfectionist contribution significant to academic procrastination by 11.7%, and (6) the locus of control and perfectionist in together contribute significant to the academic procrastination by 24.5%. The implication of this research may useful input to direct the Guidance and Counseling Teacher/Counselors to provide guidance and counseling services especially for personal and of study field. Keywords: Locus of Control, Perfectionist, Academic Procrastination